Creatine@SiO2@Fe3O4 nanocomposite as an efficient sorbent for magnetic solid‐phase extraction of escitalopram and chlordiazepoxide from urine samples through quantitation via HPLC–UV. Issue 15 (26th June 2022) - Laffafchi, Farin; Tajbakhsh, Mahmood; Sarrafi, Yaghoub; Ghani, Milad; Maleki, Behrooz
Abstract : An efficient, cost‐effective, and fast‐synthesis method is presented in the current study to prepare magnetic nanoparticles covered by cheap and nitrogen‐rich creatine. The hydrothermal method was used for the synthesis of the magnetic core. The prepared magnetic core was then covered by SiO2 and subsequently functionalized using creatine. The prepared creatine@SiO2 @Fe3 O4 was utilized as a sorbent in the magnetic solid‐phase extraction of the selected antidepressants including escitalopram and chlordiazepoxide as the model drugs. The extracted drugs were desorbed by a suitable organic solvent and analyzed by high‐performance liquid chromatography equipped with an ultraviolet detection system. The influence of different variables on the magnetic solid‐phase extraction method was examined by the Plackett–Burman and Box–Behnken designs for screening and optimization, respectively. Under the obtained optimum conditions, the linear ranges of the method were found to be in the range of 1–500 µg L –1 . The limits of detection and limits of quantification were in the range of 0.27‐0.63 µg L –1 and 0.89‐1.93 µg L –1 for the selected analytes, respectively. Furthermore, the enrichment factors were found to be 79.8 and 92.7 for chlordiazepoxide and escitalopram, respectively. The method was successfully employed for the analysis of selected drugs in urine samples.